Synthesis of glycidol from glycerol and dimethyl carbonate using ionic liquid as a catalyst - Gade, Swapna M.; Munshi, Mudassir K.; Chherawalla, Batul M.; Rane, Vilas H.; Kelkar, Ashutosh A. (Catalysis Communications, 2012)
Transesterification of dimethyl carbonate with glycerol has been investigated using various ionic liquids as catalysts. Synthesis of glycidol with high selectivity (78%) has been achieved using tetramethylammonium hydroxide ([TMA][OH]) as a catalyst at 80 degrees C. Effect of various reaction conditions on the activity and selectivity was investigated and catalyst concentration had a significant influence on conversion as well as selectivity to glycidol. Activity as well as selectivity of the catalyst decreased significantly with increase in moisture content. Recycle experiment indicated slight drop in glycerol conversion and selectivity to glycidol because of dilution of reaction mixture and also the presence of products from the initial experiment. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Glycerol carbonate; Glycidol; Ionic liquid; Transesterification of glycerol